Late Wisconsinan Morphosedimentary Sequences of the Lower Coppermine River Valley, Nunavut and Northwest Territories - St-Onge, Denis A. (Geoscience Canada, 2012)
A series of late Wisconsinan sedimentary sequences occupy parts of the Coppermine River valley, and are grouped into five morphosedimentary zones representing four environments at the time of last ice retreat: glacial, paraglacial, lacustrine and marine. The sequences commonly interfinger, and document episodic deposition in time-transgressive environments related to ice frontal positions. Glacial and paraglacial sediments are, in part, reworked in a glaciolacustrine environment extending from delta topsets of bouldery gravel to bottomset rhythmites of silt-clay. The glacial-lake rhythmites formed the matrix of a later sequence of debris-flow events, which emplaced a wedge of massive diamicton in the postglacial marine sediments. This sedimentary sequence, composed of a chaotic mass of heterogeneous material that is intimately mixed, and is accumulated in the form of a semi-fluid body in a marine environment, is possibly the best exposed Quaternary olistostrome. A general overview of the Quaternary history of the area east of Great Bear Lake and north of Point Lake shows: a) deglaciation proceeded by large-scale downwasting with no discernable readvance pulses, b) that the Coppermine River valley between Point Lake and Rocky Defile Rapids was ice-free by 10 250 14C years BP, and, c) that earth-shaping processes were intensely active for a short period at the time of deglaciation; since then the landscape has been mostly quiescent. SOMMAIRE Des séquences sédimentaires de la fin du Wisconsinien qui occupent des sections de la vallée de la rivière Coppermine définissent cinq zones morphosédimentaires représentant quatre environnements différents du retrait glaciaire, soit les milieux glaciaire, paraglaciaire, lacustre et marin. Ces séquences qui s’interdigitent souvent, documentent des épisodes sédimentaires de milieux qui varient avec le temps et les changements de position du front glaciaire. Les sédiments glaciaires et paraglaciaires sont en partie remaniés dans des milieux glaciolacustres allant des lit topset deltaïques de gravier à blocs jusqu’à des rythmites de limon-argile. Les rythmites glacio-lacustres constituent la matrice d’une séquence subséquente de lave torrentielle, qui a déposé un énorme prisme de diamictons dans les sédiments marins postglaciaires. Cette séquence sédimentaire, composée d’une masse chaotique de matériaux hétérogènes intimement mélangés accumulée sous forme semi-fluide en milieu marin, est peut-être le meilleur affleurement d’olistostrome quaternaire. Un coup d’œil sur l’histoire du Quaternaire de la région à l’est du Grand lac de l’Ours et au nord du lac Point, montre : a) que la déglaciation s’est déroulée par fonte du glacier sans réavancée discernable, b) que la vallée de la rivière Coppermine entre le lac Point et les rapides de Rocky Defile était libre de glace vers 10 250 14C BP, et c) que les mécanismes d’érosion ont été intenses pendant une courte période au moment de la déglaciation; depuis lors, le paysage est demeuré relativement statique.